Long non‐coding RNA ADAMTS9‐AS1 suppresses colorectal cancer by inhibiting the Wnt/β‐catenin signalling pathway and is a potential diagnostic biomarker. Issue 19 (5th September 2020) - Li, Ning; Li, Juan; Mi, Qi; Xie, Yan; Li, Peilong; Wang, Lili; Binang, Helen; Wang, Qing; Wang, Yanlei; Chen, Yingjie; Wang, Yunshan; Mao, Haiting; et al.
Abstract: Long non‐coding RNAs (lncRNAs) have come out as critical molecular regulators of human tumorigenesis. In this study, we sought to identify and functionally characterize lncRNAs as potential mediators of colorectal cancer progression. We screened and identified a novel lncRNA, ADAMTS9‐AS1, which was significantly decreased in colorectal cancer tissues and was correlated with clinical outcome of patients according to The Cancer Genome Atlas (TCGA) database. In addition, ADAMTS9‐AS1 regulated cell proliferation and migration both in vitro and in vivo. Bioinformatics analysis revealed that overexpression of lncRNA‐ADAMTS9‐AS1 preferentially affected genes that were linked to proliferation and migration. Mechanistically, we found that ADAMTS9‐AS1 obviously suppressed β‐catenin, suggesting that Wnt signalling pathway participates in ADAMTS9‐AS1‐mediated gene transcriptional regulation in the suppression of colorectal tumorigenesis. Finally, we found that exosomal ADAMTS9‐AS1 could serve as a diagnostic biomarker for colorectal cancer with AUC = 0.835 and 95% confidence interval = 0.777‐0.911. Our data demonstrated that ADAMTS9‐AS1 might play important roles in colorectal cancer by suppressing oncogenesis. Targeting ADAMTS9‐AS1 may have potential clinical applications in colorectal cancer prognosis and treatment as an ideal therapeutic target. Finally, exosomal lncRNA‐ADAMTS9‐AS1 is a promising, novel diagnostic biomarker for colorectal cancer.